The Anti-fibrotic Actions of Relaxin Are Mediated Through a NO-sGC-cGMP-Dependent Pathway in Renal Myofibroblasts In Vitro and Enhanced by the NO Donor, Diethylamine NONOate - Wang, Chao; Kemp-Harper, Barbara K.; Kocan, Martina; Ang, Sheng Yu; Hewitson, Tim D.; Samuel, Chrishan S. (Frontiers in Pharmacology, 2016)
INTRODUCTION: The anti-fibrotic hormone, relaxin, has been inferred to disrupt TGF-beta1/Smad2 phosphorylation (pSmad2) signal transduction and promote collagen-degrading gelatinase activity via a nitric oxide (NO)-dependent pathway. Here, we determined the extent to which NO, soluble guanylate cyclase (sGC) and cyclic guanosine monophosphate (cGMP) were directly involved in the anti-fibrotic actions of relaxin using a selective NO scavenger and sGC inhibitor, and comparing and combining relaxin’s effects with that of an NO donor. METHODS AND RESULTS: Primary renal cortical myofibroblasts isolated from injured rat kidneys were treated with human recombinant relaxin (RLX; 16.8nM), the NO donor, diethylamine NONOate (DEA/NO; 0.5-5uM) or the combined effects of RLX (16.8nM) and DEA/NO (5uM) over 72 hours. The effects of RLX (16.8nM) and DEA/NO (5uM) were also evaluated in the presence of the NO scavenger, hydroxocobalamin (HXC; 100uM) or sGC inhibitor, ODQ (5uM) over 72 hours. Furthermore, the effects of RLX (30nM), DEA/NO (5uM) and RLX (30nM)+DEA/NO (5uM) on cGMP levels were directly measured, in the presence or absence of ODQ (5uM). Changes in matrix metalloproteinase (MMP)-2, MMP-9 (cell media), pSmad2 and α-smooth muscle actin (α-SMA; a measure myofibroblast differentiation) (cell layer) were assessed by gelatin zymography and Western blotting, respectively. At the highest concentration tested, both RLX and DEA/NO promoted MMP-2 and MMP-9 levels by 25-33%, while inhibiting pSmad2 and α-SMA expression by up to 50% (all p<0.05 vs untreated and vehicle-treated cells). However, 5uM of DEA/NO was required to produce the effects seen with 16.8nM of RLX over 72 hours. The anti-fibrotic effects of RLX or DEA/NO alone were completely abrogated by HXC and ODQ (both p<0.01 vs RLX alone or DEA/NO alone), but were significantly enhanced when added in combination (all p<0.05 vs RLX alone). Additionally, the direct cGMP-promoting effects of RLX, DEA/NO and RLX+DEA/NO (which all increased cGMP levels by 12-16-fold over basal levels; all p<0.01 vs vehicle-treated cells) were significantly inhibited by pre-treatment of ODQ (all p<0.05 vs the respective treatments alone). CONCLUSIONS: These findings confirmed that RLX mediates its TGF-beta1-inhibitory and gelatinase-promoting effects via a NO-sGC-cGMP-dependent pathway, which was additively augmented by co-administration of DEA/NO.